Penggunaan Beberapa Jamur Antagonis Untuk Menekan Pertumbuhan Jamur Sclerotium Rolfsii Sacc. Penyebab Penyakit Rebah Kecambah Bibit Cabe - Yulfida, Ade (PEST Tropical Journal, 2003)
Using of some antagonists fungi to control Sclerotium rolfsii Sacc caused damping-off ofpepper, Ade Yulfida and Rustam. The experiment was conducted at Laboratorium of As-sessment Institute of Agricultural Technology and Screen House of Food Crop Service ofRiau Province, in March to June 2003. Two stage of assessments were in laboratory andscreen house. The experiment consisted of four treatments with five replications in com-pletely randomize design. T h e four treatments were A=Trichoderma harzianum, B =Tricfioderma coningii, C = Gliocladium sp and D = control (Sclerotium rolfsii S a c c ) . Theresult showed that antagonists fungi used were effectively control damping-off of peppercaused Sclerotium rolfsiiSacc. Using fungus of Trichodenna harzianumNasthebesWteaLl-ment in controlling damping-off pepper.